The Effect of Work Competence and Flexibility on Employee Performance with Work Motivation as an Intervening Variable - Nover Iradat Martinus Sinurat; Kusuma Chandra Kirana; E. Didik Subiyanto (Green Publisher Indonesia, 2024)
The purpose of this study is to determine the effect of Competence, Work Flexibility, and Work Motivation on Employee Performance at the Indonesian Post Office Malioboro, Special Region of Yogyakarta. This study used a non-probability sample with the most saturated sampaling technique or census with a total of 80 respondents. This research is primary data and is associative with a quantitative approach using questionnaire instruments. The result of this study is a significant influence between competence, work flexibility, work motivation on employee performance obtained from the t test and sobel test (mediation).